Optimizing Human Resource Development Strategies for Tourism SMEs - An AHP Approach - Hermawati, Adya; Tuwuh Sembhodo, Abimanyu (Jurnal Mebis, 2024)
Indonesia's tourism sector, a cornerstone of the economy, grapples with inconsistent tourist numbers. This study pinpoints critical factors for enhancing industry efficiency, balancing urgency with feasibility. A cross-sectional survey collected insights from 1,320 employees across 440 tourism SMEs in 11 East Java regions, complemented by input from 33 policymakers. Using an AHP questionnaire, the study prioritised variables, blending quantitative and qualitative data. The research highlights Quality of Work Life as pivotal for East Java's tourism SMEs and provides tailored regional recommendations regarding human resource management to address diverse industry and regional dynamics. Notably, Banyuwangi stands out as a prime target for development due to its substantial contributions and untapped potential. These insights offer stakeholders a roadmap to boost the most affecting human resource variable of tourism SMEs and implement region-specific strategies, ultimately elevating tourism SME performance and fostering growth in East Java's tourism sector. Focusing on Banyuwangi can unlock its tourism potential and drive regional and nearby cities economic prosperity